SISTEM PENGUKUR BERAT DAN TINGGI BADAN MENGGUNAKAN MIKROKONTROLER AT89S51 - Thomas, Thomas (TESLA Jurnal Teknik Elektro UNTAR, 2008)
Most people don’t know their ideal weights. For this reason, it needs the system which can measure the weight, height and can calculate ideal weight of people automatically. This paper discusses the designing and implementation of weight and height measurement to help the people know their ideal weight.